Advanced practice nurses’ daily practices delivering primary care to residents in long-term care facilities: a qualitative study - Zúñiga Franziska; Teuscher Ramona; Stoll Hansruedi; Sailer Schramm Monique; Vökt Franziska; Kotkowski Kornelia (BMC Primary Care, 2024)
Abstract Background Globally, there is a growing shortage of primary care professionals, including those who serve residents in long-term care facilities (LTCFs). In recent decades, numerous new care models have been implemented to improve these residents’ care. Many incorporate Advanced Practice Nurses (APNs) into interprofessional healthcare teams. In Switzerland, little is known about how these models function, and few facilities have integrated APNs. This study aims to explore the everyday practice of APNs employed at a medical centre in the Bernese Seeland region delivering care to LTC residents and collaborating with LTCFs staff. Methods This qualitative study uses the “Interpretive Description” methodology, which builds on existing knowledge and examines phenomena interpreted through a social constructivist approach. We conducted six semi-structured individual interviews, one semi-structured focus group interview, and an examination of secondary data. Our thematic analysis followed Braun and Clarke’s guidelines for data analysis. Results In LTCFs, APNs perform tasks similar to those of primary care physicians, e.g., patient visits and therapy adjustments, within the limits set by their supervising physicians. In addition, they contribute significantly to facility-wide quality improvement. We identified three fundamental elements for successful collaboration between APNs and LTCF staff: 1) clarifying roles and responsibilities; 2) establishing well-defined communication methods and pathways; and 3) building and maintaining trust. Together with LTCF staff, APNs provide multidimensional, person-centred care that focuses on medical, social, and nursing issues with the goal of maintaining the residents’ best possible quality of life. Conclusions Our results suggest that integrating APNs into the LTCF care system improves care quality for residents and increases staff members’ job satisfaction.